About Schmidt - Copyright Collection (Library of Congress) ([Place of publication not identified] : [Publisher not identified], 2002)
While confirming Jack Nicholson's status as an American national treasure, About Schmidt is sure to provoke polarized reactions. Stoked by the success of Election, director Alexander Payne and cowriter Jim Taylor have altered Louis Begley's novel to suit their comedic agenda, turning Nicholson's titular character into a 66-year-old, newly retired Omaha insurance actuary, weary from decades of drudgery and passionless marriage. When his wife suddenly dies, he attempts to reclaim his life in a king-sized Winnebago, desperate to convince his daughter (Hope Davis) not to marry the Denver dimwit (Dermot Mulroney) whose mother (Kathy Bates) has her own baggage of peculiar peccadilloes. Nicholson perfectly (and often hilariously) nails the seething anger beneath his character's façade of resignation, but Payne and Taylor convey cold-hearted contempt for these Midwestern malcontents. Think of this as Ikiru with bleaker humanity, until Schmidt finds meaning--and some small reward--in a quiet gesture of goodwill. Love it or hate it, About Schmidt is a movie you won't soon forget. --Jeff Shannon
Copyright: New Line Productions, Inc. Appl. au.: Avery Pix, Inc., employer for hire. Prev. reg.: Based on prev. reg. screenplay. NM: all other cinematographic material. DCR 2002; PUB 13Dec02; REG 19Mar03; PA1-127-412.
Sources used: copyright data base; copyright data sheet.
Keywords: Comedy -- Feature